PMO-020 Audit to assess the acceptability and usefulness of an audiovisual aid in the preparation of patients for outpatient endoscopy. (28th May 2012) - Williams, I; Edwards, S; Boulton, R
Abstract : Introduction: Written information is traditionally used to educate patients about endoscopy, but it is difficult to fully convey endoscopy via a leaflet. We assessed whether a video following a "patient" through the endoscopy journey was a useful tool to assist patient's understanding of endoscopy as a supplement to the information that we have been using in our Unit. Methods: A DVD showing the endoscopy process was sent to all individuals booked for an outpatient upper GI endoscopy over 2 months. On arrival at endoscopy unit they were asked to complete a questionnaire. Results: Abstract PMO-020 table 1 demonstrating responses to questions 4–6. Of 158 questionnaires, 149 replies were suitable for analysis. 81% gave the DVD top score for clarity and ease of understanding. The majority of responders found the DVD useful in preparing them for what will happen on the day of endoscopy with 81% of responders scoring the DVD one of the top two ratings for this category. All of the responders felt the DVD was a good idea and all but one individual recommended that we should continue to include it in the information packs. Conclusion: Overall, the response to the endoscopy DVD was very positive. Some of the issues related to not watching the DVD will likely be solved once it is in use in an endoscopy pre-admission clinic. On the basis of this extremely positive result, we plan to utilise the endoscopy information DVD more widely and extend it to other endoscopic procedures. Competing interests: None declared.